KOMPARASI MINAT BELAJAR SISWA ANTARA PEMBELAJARAN DARING DENGAN PEMBELAJARAN TATAP MUKA PADA MATA PELAJARAN GEOGRAFI KELAS XI IPS DI SMA NEGERI 1 SUTERA KABUPATEN PESISIR SELATAN - Dina Istifiari; Surtani Surtani (JURNAL BUANA, 2022)
The purpose of this study is to describe, analyze and discus data about: the comparison of student interest in learning between online learning and face to face learning in Geography class XI IPS at SMA Negeri 1 Sutera, Pesisir Selatan Regency. This research belongs to a comparative study with the ex post facto approach. The sampling technique used was purposive sampling with a sample size of 34 students. This research was conducted at SMAN 1 Sutera. The data collection thecniques used were questionnaires and documentation. It is necessary to test the validity and reliability of the instrument because one of the research variables, namely student interest in learning, is a psychological variable. The data analysis technique used is the respondent achievement level (TCR) data analysis technique and the t tes. The results showed that: 1) The average score of student interest in face to face learning wa 3,31 with a respondent achievement level (TCR) of 82,8% with a high category compared to the average score of the student interest in learning in online learning, namely 2,62 with the responden achievement level (TCR) of 65,4% with the moderate category. 2) the results of the hypothesis test t-count > t-table (5,65 >1,49) at the significant level ɑ 0,05. This means that the proposed hypothesis is accepted (H1 is accepted, H0 is rejected)